State and Church in Russian Empire in 1725—1730: Political Aspect of Relations (on Example of Nizhny Novgorod Diocese) - A. V. Bodrin (Научный диалог)
The article deals with the issue of relations between the state and the church in the Russian Empire in 1725—1730 in the political sphere. Attention is paid to the preservation of the former policy of the state represented by the Synod in relation to the local episcopate. On the example of the Nizhny Novgorod region, a general description of the organization of the diocesan administration is given with a description of a number of changes that have occurred; the versatile activity of Archbishop Pitirim, who lost the reliable support of Peter I in connection with his death and is now faced with serious challenges, is considered in the article. The results of the analysis of problems in the relationship between secular and spiritual authorities in political terms are presented. A classification of these problems is proposed on the basis of a generalized analysis of the entire range of issues that have become the object of contradictions between the state and the church. Particular attention is paid to problems that were of a financial, economic and administrative-legal nature. It is shown on the basis of regional material that on a number of issues it was clearly not enough for the adoption of this or that decision at the level of the Synod, and the local bishops needed a resolution of the Senate. It is proved that the problems of church-state relations, laid down under Peter I, retained their relevance during subsequent reigns.